2012
DOI: 10.1186/0778-7367-70-8
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional status of school-age children - A scenario of urban slums in India

Abstract: BackgroundOne of the greatest problems for India is undernutrition among children. The country is still struggling with this problem. Malnutrition, the condition resulting from faulty nutrition, weakens the immune system and causes significant growth and cognitive delay. Growth assessment is the measurement that best defines the health and nutritional status of children, while also providing an indirect measurement of well-being for the entire population.MethodsA cross-sectional study, in which we explored nut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
178
9
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 213 publications
(217 citation statements)
references
References 21 publications
24
178
9
6
Order By: Relevance
“…It was observed that prevalence of underweight was higher amongst pupils whose parents were unemployed (66.7%) amongst pupils whose mothers were unemployed and 60% amongst pupils whose fathers were unemployed.) this is in keeping with findings elsewhere 12,14,17 and goes to show that economically empowered parents provide better nutrition and health for their offsprings. Ahmed confirmed that better economic situation can be a primary cause for better growth of school children because economic situation usually influences the kind and quantity of food consumed 18 .Most fathers (63.6%) had secondary level of education, while most mothers had primary level of education (46.6%) this could explain the low prevalence of under nutrition seen in our study as compared to other studies 12,14,19, .Concerning educational status; the mothers' education plays a major role in determining the nutritional status of children 14,19 .In agreement with most studies low maternal education is a major determinant of malnutrition 13,16 .…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…It was observed that prevalence of underweight was higher amongst pupils whose parents were unemployed (66.7%) amongst pupils whose mothers were unemployed and 60% amongst pupils whose fathers were unemployed.) this is in keeping with findings elsewhere 12,14,17 and goes to show that economically empowered parents provide better nutrition and health for their offsprings. Ahmed confirmed that better economic situation can be a primary cause for better growth of school children because economic situation usually influences the kind and quantity of food consumed 18 .Most fathers (63.6%) had secondary level of education, while most mothers had primary level of education (46.6%) this could explain the low prevalence of under nutrition seen in our study as compared to other studies 12,14,19, .Concerning educational status; the mothers' education plays a major role in determining the nutritional status of children 14,19 .In agreement with most studies low maternal education is a major determinant of malnutrition 13,16 .…”
Section: Discussionsupporting
confidence: 68%
“…This could be explained by the fact that younger children are better fed when compared to their older siblings. Majority of the pupils 65.4% were from monogamous families, while the rest were from polygamous families, this is similar to work done in Bangalore India were more pupils 55.4% were from monogamous families but differs from what was obtained in Bareilly, India were 73% of the pupils were from polygamous homes 10,14 .Although there was no statistical difference between the family type and nutritional status, we observed that the prevalence of underweight was higher (39.3%) amongst children from polygamous homes were when compared to those from monogamous 18.4% it follows that more pupils 78.2% from monogamous families had healthy nutrition when compared to the 57.6% from polygamous families. This is similar to work done in Abeokuta, Nigeria and Brailley 14,15 .…”
Section: Discussionsupporting
confidence: 68%
“…Childhood undernutrition is a global health challenge impacting child growth and survival rates, contributing to future increased chronic disease prevalence, and reducing individual and national economic productivity (Black et al., 2013; Chang, Walker, Grantham‐McGregor, & Powell, 2002; Srivastava, Mahmood, Srivastava, Shrotriya, & Kumar, 2012). Childhood undernutrition is embedded within the complexities of intersectoral and multilevel interfaces related to food security and equities in health.…”
Section: Introductionmentioning
confidence: 99%
“…To assess nutritional status, CDC weight-for-age, stature-forage and body mass index-for-age percentile growth charts were used. Other variables checked for health and nutritional status were physical signs and symptoms [11] including eyes, nails, teeth, hair and skin examination; stool character and pattern; current eye, skin or respiratory allergy/infection or nervous disorder; and frequency of severe sickness [12,13]. Besides this, the socio-demographic data was also collected to check the sample on inclusion and exclusion criteria.…”
Section: Instrumentationmentioning
confidence: 99%